Coherent Raman Scattering Microscopy for Evaluation of Head and Neck Carcinoma. (September 2017) - Hoesli, Rebecca C.; Orringer, Daniel A.; McHugh, Jonathan B.; Spector, Matthew E.
Objective: We aim to describe a novel, label-free, real-time imaging technique, coherent Raman scattering (CRS) microscopy, for histopathological evaluation of head and neck cancer. We evaluated the ability of CRS microscopy to delineate between tumor and nonneoplastic tissue in tissue samples from patients with head and neck cancer. Study Design: Prospective case series. Setting: Tertiary care medical center. Subjects and Methods: Patients eligible were surgical candidates with biopsy-proven, previously untreated head and neck carcinoma and were consented preoperatively for participation in this study. Tissue was collected from 50 patients, and after confirmation of tumor and normal specimens by hematoxylin and eosin (H&E), there were 42 tumor samples and 42 normal adjacent controls. Results: There were 42 confirmed carcinoma specimens on H&E, and CRS microscopy identified 37 as carcinoma. Of the 42 normal specimens, CRS microscopy identified 40 as normal. This resulted in a sensitivity of 88.1% and specificity of 95.2% in distinguishing between neoplastic and nonneoplastic images. Conclusion: CRS microscopy is a unique label-free imaging technique that can provide rapid, high-resolution images and can accurately determine the presence of head and neck carcinoma. This holds potential for implementation into standard practice, allowing frozen margin evaluation even at institutions without a histopathology laboratory.